(untitled) (OODBODHAN, 2026)
Nanofluids and turbulators have gained significant interest because they improve heat transfer. Experimental investigations were performed using 12 mm and 18 mm pitch helical coil turbulator along with CuO-water nanofluids on counter flow concentric heat exchanger. CuO nanoparticles were synthesized using sol-gel process and two-step process was used to prepare CuO-water nanofluids of 0.025% volume concentration. The concentric heat exchanger was designed, where hot fluid at 70⁰ C flowed at 5.01 LPM and cold fluid at 25⁰ C circulated through the inner tube at 5.60-10.4 LPM. Experimental findings reveal that dispersing CuO nanoparticles in water led to enhancements in heat transfer. Overall heat transfer coefficients for CuO-nanofluid is increased by 5-8.64 % across flow rates 5.60-10.4 LPM compare to pure water. The study shows that 12 mm turbulator enhanced more heat transfer than 18 mm turbulator in pure water and nanofluids. Overall heat transfer coefficients for 18 mm turbulator and 12 mm turbulator increased by 24.66-31.18%; 36-47.08 % respectively and pressure drop increased by 309.09-560%; 454.55-716 % respectively across flow rates ranging from 5.60-10.4 LPM compare to water without turbulator. The highest overall heat transfer coefficients was found 51.01 % for CuO-water nanofluids with 12 mm turbulator at 10.4 LPM compare to CuO-water nanofluids without turbulator. Overall, the findings indicate that smaller-pitch helical turbulator intensify turbulence and CuO nanoparticles improves thermal properties of water thereby improving heat transfer, although it results in a noticeable rise in pressure losses.